The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1007/bf02849707
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hearing impairment among rural and urban school going children: A survey

Abstract: A total of 1,670 school going children (urban 1030 and rural 640) in the age range of 12-14 years were screened for hearing loss during a survey conducted by the Department of Otolaryngology of the Postgraduate Institute of Medical Education & Research, Chandigarh. 6.31% of cases in the urban group were found to be having hearing loss as compared to 32.81% of cases in the rural group. Secretory otitis media was found to be the commonest cause of hearing impairment in both the urban and rural group accounting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2001
2001
2106
2106

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…Similar to present study, a prevalence of hearing impairment of 19.56% has been reported in a study conducted among 12-14 years age school children in Chandigarh. 5 The prevalence of hearing impairment of 13.05% has been reported in a study conducted among 339 kindergarten school children in Mangalore, India. 6 In an another study conducted among 1200 school children of age 4-17 years in Pune, India, about 11.8% children were found to be suffering from deafness which is lower than ours.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to present study, a prevalence of hearing impairment of 19.56% has been reported in a study conducted among 12-14 years age school children in Chandigarh. 5 The prevalence of hearing impairment of 13.05% has been reported in a study conducted among 339 kindergarten school children in Mangalore, India. 6 In an another study conducted among 1200 school children of age 4-17 years in Pune, India, about 11.8% children were found to be suffering from deafness which is lower than ours.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several investigators have stressed that the prevalence of HL may vary between subgroups within a given population. Racial factors may play a role in some of these observed differences; however, they do not account for differences seen within racially homogenous populations 11,12 . For example, one study of school children in India demonstrated a mild HL in 6.3% of children in an urban school and 32.8% of children in a neighboring rural community 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the most common cause of HL is conductive loss secondary to treatable causes such as cerumen impactions, otitis media (OM), and other middle ear pathologies (10). Much of the sensorineural HL in developing countries is also preventable, with major preventable causes, including genetic HL associated with consanguinity in some regions, infections for which there are effective vaccinations (measles, mumps, rubella, meningitis), use of ototoxic drugs, exposure to high levels of noise, and limited access of pregnant women to prenatal, perinatal, and postnatal health care.…”
Section: The Global Impact Of Hearing Impairmentmentioning
confidence: 99%